1) Aplicando as regras práticas, elimine os parênteses nas expressões: a) - (+ 10) = b) -(-5) = c) + (-16) = d) + (+ 12) = e) -(-25) = f) -(+30) = g) -(-3+ 2) = h) + (-5+3) = i) -(4-7)=+(6-2)=-(2-5)=+(-1-10)=
Anexos:
Respostas
respondido por:
1
Resposta:
a) -10
b) +5
c) -16
d) +12
e) +25
f) -30
g) -(-1) = +1
h) +(-2) = -2
i) -(-3) = +3
j) +(+4) = +4
k) -(-7) = +7
l) +(-11) = -11
Perguntas similares
3 anos atrás
3 anos atrás
5 anos atrás
5 anos atrás
5 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás